Uji Aktivitas Antibakteri Ekstrak n-Heksana Biji Buah Langsat (Lansium domesticum Corr ) Terhadap Bakteri Escherichia coli secara In Vitro - ., Agus Hendra Rao Timoteus (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background: The role of medical plants today is more evident with theincrease of knowledge of the properties of various plants that are thecultural heritage of the nation. Langsat (Lansium domesticum Correa) isone of the local plants that have the potential to be developed, langsat hasmany uses and benefits, one of which is used to treat diarrhea. The mostcommon bacteria that cause diarrhea is Escherichia coli. The resistancerates of E. coli is still increasing overtime, so the need to find analternative antibacterial that sensitive to E. coli in necessary .Â Objectives:This study aims to determine the antibacterial activity of n-hexane extractof langsat seeds against Escherichia coli, to determineÂ the content ofsecondary metabolites contained in the extract, to determine minimuminhibitory concentration (MIC), and minimum bactericidal concentration(MBC) of extract againts Escherichia coli. Methodology: Langsat seedsextracted using maceration method with solvent n-hexane. Testantibacterial activity against Escherichia coli bacteria using a tube dilutionmethod to determine the MIC and MBC. Result: Based on phytochemicalscreening, n-hexane extract containing saponin compounds and terpenoidcompounds. MIC extract n-hexane can not be determined, and n-hexaneextract of langsat seeds does not have MBC againts Escherichia coli.Conclusion: Extract n-hexane of langsat seed has no antibacterial activityagainst Escherichia coli.Keywords: antibacterial, Langsat seed, Escherichia coli. 1) Medical School, Faculty of Medicine, University of TanjungpuraPontianak, West Borneo. Â 2) Biology School, Faculty of Mathematic and Scientific, University ofTanjungpura Pontianak, West Borneo. 3) Medical School, Faculty of Medicine, University of TanjungpuraPontianak, West Borneo.